Theoretical and Methodological Aspects of Cost Analysis - Aitimbetov , Koyshibek (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article discusses the theoretical and methodological aspects of cost analysis. In particular, it highlights the main tasks of product cost analysis, as well as issues such as production costs and the objects of product cost analysis.